Tales from the German. Volume II. - Velde, C. F. van der (Carl Franz), 1779-1824; Greene, Nathaniel, 1797-1877 (Salt Lake City, UT : Project Gutenberg, 2010)
"Tales from the German. Volume II." by C. F. van der Velde is a collection of translated stories written in the early 19th century. This volume includes historical tales set against the backdrop of significant events like the Thirty Years War and the Reformation. The stories explore themes of faith, struggle, and human emotion through the lives of various characters, such as Katharine, a devoted mother, and the troubled book-keeper, Oswald Dorn, who grapple with the tumultuous times they live in. At the start of this volume, the narrative unfolds on Christmas Eve during the year 1628 in Schweidnitz, focusing on Katharine, the wife of merchant Fessel, as she prepares gifts for her family amidst the looming threat of religious conflict. The opening scene reveals her interactions with Oswald Dorn, who shares a somber outlook regarding the religious persecution growing in their region. As the story progresses, tensions rise with the impending arrival of troops that embody the dangers of the era, unveiling a tale rife with impending conflict, personal relationships, and the struggle to maintain faith and hope against adversity. (This is an automatically generated summary.)
The Lichtensteins: a tale of the times of the thirty years war -- The sorceress -- The anabaptist: a tale of the first half of the sixteenth century.
Release date is 2010-05-19
Produced by Charles Bowen, from page scans provide by the Web Archive
Keywords: German fiction -- Translations into English